Pengaruh Electronic Word of Mouth, Harga dan Promosi Penjualan Terhadap Keputusan Pembelian di Online Shop Lazada (Studi Kasus Pada Masyarakat Kota Padang) - Abi Bakri Nasution; Tri Kurniawati (Universitas Negeri Padang, 2022)
This study aims to determine: (1) impact of electronic word of mouth on purchasing decisions Lazada (2) impact of prices on purchasing decisions in Lazada (3) impact of sales promotions on purchasing decisions in Lazada. This is quantitative research with a sample of 97 people in the city of Padang. Data is collected by using a questionnaire. The methods of data analysis used are descriptive analysis and multiple regression. The results show that Electronic Word of Mouth, Sales Promotion have a significant effect on Lazada purchasing decisions, while the price has no significant effect on Lazada purchasing decisions (a case study on the Padang City).